The disappointed bridge : Ireland and the post-colonial world - Pine, Richard (Cambridge Scholars Publishing, 2014)
This original study is the first major critical appraisal of Ireland's post-colonial experience in relation to that of other emergent nations. The parallels between Ireland, India, Latin America, Africa and Europe establish bridges in literary and musical contexts which offer a unique insight into independence and freedom, and the ways in which they are articulated by emergent nations. They explore the master-servant relationship, the functions of narrative, and the concepts of nationalism, m ...